2020
DOI: 10.1108/sr-05-2020-0125
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective piezoresistive sensor for mercury (Hg2+) ions detection using mercaptosuccinic acid-functionalized microcantilevers with cross-linked pyridinedicarboxylic acid

Abstract: Purpose This paper aims to report an insightful portable microfluidic system for rapid and selective sensing of Hg2+ in the picomolar (pM) concentration using microcantilever-based piezoresistive sensor. The detection time for various laboratory-based techniques is generally 12–24 h. The majority of modules used in the proposed platform are battery oriented; therefore, they are portable and handy to carry-out on-field investigations. Design/methodology/approach In this study, the authors have incorporated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Figure 3 c is the height scope of the microcantilever; it can be seen that the microcantilever bent upward for 36.122 μm and the depth of the reactive well is 40.534 μm. Since the coefficient of thermal expansion for PI is higher than that of Si in this temperature range, the tensile stresses in the PI films [ 14 ] made the microcantilever bend upward, which can inhibit the microcantilever from sticking to the bottom of the reactive well.…”
Section: Design and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 c is the height scope of the microcantilever; it can be seen that the microcantilever bent upward for 36.122 μm and the depth of the reactive well is 40.534 μm. Since the coefficient of thermal expansion for PI is higher than that of Si in this temperature range, the tensile stresses in the PI films [ 14 ] made the microcantilever bend upward, which can inhibit the microcantilever from sticking to the bottom of the reactive well.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…In 2020, Rotake et al studied a piezoresistive microcantilever for Hg 2+ detection with a limit of 0.75 ng/mL. The spring constant of the microcantilever was 0.07053 N/m [ 14 ]. In 2020, Kandpal et al reported a piezoresistive microcantilever which realized a 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) detection with 6-MNA surface functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…From comparison Table 1, it is clear that this technique has the potential and capability to selectively detect Hg 2+ ions with a limit of detection (LOD) of as low as 0.21 nM and hence it outperforms the other methods. Nevertheless, the method proposed by Rotake et al 40 have outstanding potential for the detection of mercury at the picomolar range but require costly and sophisticated analytical tools for the measurements. Moreover, Qi et al 41 used the colorimetric technique for selective Hg 2+ detection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,7 Accordingly, they have a wide range of applications in detecting numerous biologically and environmentally relevant cations, such as mercury, lead, and calcium ions, as well as hydrocarbons in water. [7][8][9][10][11] In addition, they can be used as highly sensitive humidity and temperature sensors. 11,12 Silicon microcantilever-based MEMS sensors are also promising for medical recognition and detection of a wide range of viruses that are transferable from one human to another, such as human immunodeficiency virus and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; COVID-19).…”
Section: Introductionmentioning
confidence: 99%
“…Microcantilever‐based MEMS sensors have several advantages owing to their rapid response, high sensitivity, low cost, user‐friendliness, lightweight, portability, and implementation flexibility in sensing arrays 3,7 . Accordingly, they have a wide range of applications in detecting numerous biologically and environmentally relevant cations, such as mercury, lead, and calcium ions, as well as hydrocarbons in water 7–11 . In addition, they can be used as highly sensitive humidity and temperature sensors 11,12 .…”
Section: Introductionmentioning
confidence: 99%